THE COST OF UNEMPLOYMENT - Abrorjon Habibullayev Ahmadali ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Losing a job can be the most distressing economic event in a person’s life. Most people rely on their labour earnings to maintain their standard of living, and many people get from their work not only income but also a sense of personal accomplishment. This article begins our study of unemployment. The problem of unemployment is usefully divided into two categories – the long-run problem and the short-run problem. In this chapter we discuss the determinants of the long-run problem – an economy’s natural rate of unemployment. As we will see, the designation natural does not imply that this rate of unemployment is desirable. Nor does it imply that it is constant over time or impervious to economic policy. It merely means that this unemployment does not go away on its own, even in the long run.